Anti-Cancer Strategies Using Anaerobic Spore-Forming Bacteria Clostridium: Advances and Synergistic Approaches - Saloni Singh; Geun-Hyung Kim; Kwang-Rim Baek; Seung-Oh Seo (Life)
Despite ongoing advancements, cancer remains a significant global health concern, with a persistent challenge in identifying a definitive cure. While various cancer therapies have been developed and approved, offering treatments for smaller neoplasms, their efficacy diminishes in solid tumors and hypoxic environments, particularly for chemotherapy and radiation therapy. A novel approach, Clostridium-based therapy, has emerged as a promising candidate for current solid tumor treatments due to its unique affinity for the hypoxic tumor microenvironment. This review examines the potential of Clostridium in cancer treatment, encompassing direct tumor lysis, immune modulation, and synergistic effects with existing cancer therapies. Advancements in synthetic biology have further enhanced its potential through genetic modifications, such as the removal of alpha toxin gene from Clostridium novyi-NT, the implementation of targeted approaches, and reduction in systemic toxicity. Although preclinical and clinical studies have demonstrated that Clostridium-based treatments combined with other therapies hold promise for complete cancer eradication, challenges persist. Through this review, we also propose that the integration of various methods and technologies together with Clostridium-based therapy may lead to the complete eradication of cancer in the future.